Good Corporate Governance, Leverage and Corporate Financial Performance in the Jakarta Islamic Index - Puteri, Hesi Eka (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to estimate the effect of Good Corporate Governance and Leverage on the Financial Performance of companies listed on the Jakarta Islamic Index in 2016 to 2020. Methodology/approach – This study is a confirmatory research with a quantitative approach. The secondary data in this study obtained from the Jakarta Islamic Index (JII), with a total sample of 14 companies registered in the analysis period and have complete data related to the variables studied. Panel data regression analysis was used in this study by selecting the Random Effect Model as the estimation method. Findings – It was found that institutional ownership, which is one of the measurement proxies for Good Corporate Governance, has a positive effect on variations in the company's financial performance achievements. This study has proven that institutional ownership has an important role in minimizing agency conflicts that occur between managers and shareholders. If institutional ownership is implemented properly and in line with the company's vision, the financial performance will be excellent and in the long-term financial sustainability will be created. Novelty/value – This study proves that institutional ownership is a driving factor in increasing corporate financial performance proxied by Return on Equity (ROE).